Economics, externalities and rare disease - Carlisle Ford Runge; James Campbell; Carlisle P. Runge; Reena V. Kartha (Rare)
Special combined efforts addressing rare diseases should apply economic principles and methods to maximize returns to research and investment. Four opportunities exist: (1) exploiting treatment spillovers; (2) encouraging institutional networking and knowledge-sharing; (3) recognizing shared molecular and genetic etiologies; (4) organizing resulting clusters and baskets for scaling trials, research, diagnosis and treatment.